Effect of Increasing 3% Oil Corn Dried Distillers Grains with Solubles on Nursery and Finishing Pig Growth Performance and Carcass Characteristics - Rachelle Lazaga; Hilario M. Cordoba; Katelyn N. Gaffield; Robert D. Goodband; Jordan T. Gebhardt; Mike D. Tokach; Joel M. DeRouchey; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2024)
Two experiments were conducted to determine the effects of increasing 3% oil corn dried distillers grains with solubles (DDGS) on nursery and finishing pig performance. In exp. 1, a total of 355 barrows (DNA 200 × 400; initially 27.2 ± 0.40 lb) were used in a 21-d growth trial with four or five pigs per pen and 18 replicate pens per treatment. Pigs were fed a corn-soybean meal-based diet with 0, 10, 20, or 30% corn DDGS. Overall, final BW, ADG, and ADFI decreased (linear, P < 0.05) resulting in a tendency (quadratic, P < 0.10) for poorer F/G with increasing DDGS. Caloric efficiency tended (quadratic, P < 0.10) to decrease with increasing DDGS suggesting that the initial estimate for the NE of DDGS at 899 kcal/lb was underestimated. Using the observed performance, the NE of DDGS would need to be 1,006 kcal/lb for caloric efficiency to be equal across treatments. In exp. 2, a total of 684 pigs (DNA 241 × 600, initially 89.9 ± 1.20 lb) were used in a 97-d trial with nine or 10 pigs per pen and 18 replicate pens per treatment. Pigs were fed a corn-soybean meal-based diet with 0, 10, 20, or 30% DDGS. Overall, as DDGS increased, final BW and ADG decreased (linear, P < 0.001) while ADFI tended (linear, P < 0.057) to decrease, which results in poorer F/G (linear, P < 0.001). Caloric efficiency based on a live- or carcass –weight basis decreased (linear, P ≤ 0.058) as DDGS increased. The NE of DDGS would need to be 1,001 kcal/lb for live weight, and 963 kcal/lb for carcass weight for caloric efficiency to be equal across treatments. For the final marketing event, carcass yield, HCW, and backfat depth decreased (linear, P ≤ 0.001) as DDGS increased. Percentage lean and carcass IV increased (linear, P < 0.001) with increasing DDGS. Additionally, dry matter and N digestibility decreased (linear, P < 0.001) with increasing DDGS. In conclusion, increasing 3% oil DDGS in nursery and finishing pig diets negatively affected growth performance, carcass IV, and DM and N digestibility. Using caloric efficiency calculations, the NE content of 3% oil DDGS is estimated to be between 1,001 kcal/lb for live-weight and 963 kcal/lb for carcass-weight caloric efficiency for growing finishing pigs.
Keywords: Dried distillers grains with solubles; growing pigs; iodine value; nursery pigs; oil